State Capture Analysis : A How to Guide for Practitioners - Raballand, Gael; Rijkers, Bob (World Bank, Washington, DC, 2021)
This note describes how political economy analysis can be used to promote development, focusing specifically on state capture. It is intended to help practitioners within the World Bank execute and disseminate political economy analysis of state capture. It is not intended to be comprehensive but serves as a how-to guide for those not intimately familiar with the topic.